Advertising and promotion an integrated marketing communications perspective - Belch, George E. (George Edward) 1951-; Belch, Michael A. (Boston McGraw-Hill Irwin, 2009)
This work continues its advertising focus with an emphasis on IMC. It is the first book to reflect the shift from the conventional methods of advertising to the more widely recognised approach of implementing an IMC strategy.
Part 1. The role of IMC in marketing -- Chapter 1. An introduction of integrated marketing communications -- Chapter 2. The role of IMC in the marketing process -- Part 2. Integrated marketing program situation analysis -- Chapter 3. Organizing for advertising and promotion -- Chapter 4. Perspectives on consumer behavior -- Part 3. Analyzing the communication process -- Chapter 5. The communication process -- Chapter 6. Source, message, and channel factors -- Part 4. Objectives and budgeting for integrated marketing communications programs -- Chapter 7. Establishing objectives and budgeting for the promotional program -- Part 5. Developing the integrated marketing communications program -- Chapter 8. Creative strategy. planning and development -- Chapter 9. Creative strategy. implementation and evaluation -- Chapter 10. Media planning and strategy -- Chapter 11. Evaluation of broadcast media -- Chapter 12. Evaluation of print media -- Chapter 13. Support media -- Chapter 14. Direct marketing and marketing on the Internet -- Chapter 15. Internet and WWW -- Chapter 16. Sales promotion -- Chapter 17. Public relations, publicity, and corporate advertising -- Chapter 18. Personal selling -- Part 6. Monitoring, evaluation, and control -- Chapter 19. Measuring the effectiveness of the promotional program -- Part 7. Special topics and perspectives -- Chapter 20. International advertising and promotion -- Chapter 21. Regulation of advertising and promotion -- Chapter 22. Evaluating the social, ethical, and economic aspects of advertising and promotion.
Keywords: Advertising; Sales promotion; Communication in marketing